PERSEPSI GURU SEKOLAH DASAR TERHADAP JABATAN FUNGSIONAL GURU - Endro Wahyuno (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
The purposes of this research were to describe teachers’ perception toward teachers’ functional job promotion, teachers’ experience related to contraints in achieving functional job promotion, teachers’ efforts in solving problems related to contraints in achieving functional job promotion. Population of the research was elementary schools’ teachers at Malang Regent. The subjects were 187 teachers selected by multi stage random sampling. The instruments were a questionnaire and documentation. The collected data was analysed by procentage. The result found that teachers’ perception was positive toward func¬tional job promotion. Generally, teachers’ constraints experience related to contraints in achieving func¬tional job promotion were in an education field and scientific writing field. Teachers solved the contrains by themselves.